2010
DOI: 10.1111/j.1365-2362.2010.02357.x
|View full text |Cite
|
Sign up to set email alerts
|

Lipid assessment, metabolic syndrome and coronary heart disease risk

Abstract: In this European study population, the TC/HDL-C, apoB/apoA-I and LDL(NMR) /HDL(NMR) ratios were similarly associated with components of the metabolic syndrome and CHD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 29 publications
(29 reference statements)
3
11
0
Order By: Relevance
“…As a CVD risk management tool, LDL-C values indicate which patients have lowered their risk to acceptable levels (as inferred from their treatment goal having been reached) and which have not (indicating a need for more aggressive treatment). Several large clinical studies demonstrate the limitations of this strategy in that, when alternate measures of LDL are discordant, LDL-P is more strongly associated with incident CVD events than LDL-C [5,6,[9][10][11][12][13][14][15][16][17][18]. Consequently, several expert panels now recommend consideration of LDL-P levels to adjudicate and guide medical decision-making [19][20][21].…”
Section: Introductionmentioning
confidence: 95%
“…As a CVD risk management tool, LDL-C values indicate which patients have lowered their risk to acceptable levels (as inferred from their treatment goal having been reached) and which have not (indicating a need for more aggressive treatment). Several large clinical studies demonstrate the limitations of this strategy in that, when alternate measures of LDL are discordant, LDL-P is more strongly associated with incident CVD events than LDL-C [5,6,[9][10][11][12][13][14][15][16][17][18]. Consequently, several expert panels now recommend consideration of LDL-P levels to adjudicate and guide medical decision-making [19][20][21].…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, there have been studies reporting that osteoporosis is associated with atherosclerosis or calcification of the arteries,9-12) and that low BMD is significantly associated with greater cardiovascular mortality 13). Given that high LDL-C or low high density lipoprotein cholesterol (HDL-C) are main risk factors for atherosclerosis and cardiovascular disease,14) it could be hypothesized that serum lipid profiles are significantly associated with BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that approximately 50% of population-attributable risk of developing CVD is associated with abnormalities in lipid biomarker profile (5). Most of the existing guidelines have used traditional lipid levels and other risk factors, namely total cholesterol (TC), LDL cholesterol (LDL-C), HDL cholesterol (HDL-C), triglycerides (TG), and nonlipid risk factors, e.g., high blood pressure, cigarette smoking, diabetes, age, sex, diet, and obesity, as risk factor scores for CVD risk prediction (6, 7).…”
mentioning
confidence: 99%
“…Most of the existing guidelines have used traditional lipid levels and other risk factors, namely total cholesterol (TC), LDL cholesterol (LDL-C), HDL cholesterol (HDL-C), triglycerides (TG), and nonlipid risk factors, e.g., high blood pressure, cigarette smoking, diabetes, age, sex, diet, and obesity, as risk factor scores for CVD risk prediction (6, 7). Based on recent studies, there is a growing interest to investigate whether nontraditional lipid-related markers add incremental value to standard prognostic models containing information on TC, HDL-C, and other conventional risk factors and can improve the CVD risk prediction (5). The utility of nontraditional markers in risk assessment is best examined by combining them with a model that includes traditional risk factors (8, 9).…”
mentioning
confidence: 99%